Особливості вивчення природничо-наукових дисциплін бакалаврами з психології - Хавіна, Ірина Валер'ївна (НТУ "ХПІ", 2017)
У статті розглядаються дисципліни природничого циклу в професійній підготовці бакалаврів з психології. Детально розглянуто, якими особливостями володіють природничі дисципліни в процесі навчання бакалаврів з психології. Розкрито значення кожної природничої дисципліни в процесі навчання майбутніх психологів. Проаналізовано результати анкетування студентів першого курсу напряму "психолог".

The article deals with the disciplines of the natural science cycle in the professional training of bachelors in psychology. It is considered in detail what features natural science disciplines have in the process of training bachelors and psychologists. The significance of each natural science discipline is revealed in the process of training future psychologists. The results of the questionnaire survey of the first year students of the "psychologist" direction are analyzed.
Features of the study of natural science disciplines bachelors with psychology
Keywords: професійна підготовка; природничі дисципліни; систематичність; професійна діяльність; vocational training